PENGARUH LIKUIDITAS, SOLVABILITAS, DAN AKTIVITAS TERHADAP PROFITABILITAS PADA SUB SEKTOR PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Ni Putu Indah Wardani; Gde Herry Sugiarto Asana; Made Christin Dwitrayani (UNHI Press, 2024)
Abstract: This research aims to determine the effect of liquidity, solvency and activity on profitability both simultaneously and partially. The research design used was clause quantitative. The research population is Coal Mining Sub Sector Companies listed on the Indonesia Stock Exchange. The sample in the study was 66 samples from 22 company financial reports. The data used in this research is secondary data. Secondary data in this research is in the form of annual financial reports for the Coal Mining Sub Sector listed on the Indonesia Stock Exchange for 2020-2022. Data was collected through document recording, then analyzed using multiple linear regression analysis using SPSS Version 23 tools. The research results showed that (1) liquidity, solvency and activity simultaneously had a significant effect on profitability, (2) liquidity and solvency partially had a negative effect and significant to profitability, (3) activities partially have a positive effect on profitability in Coal Mining Sub Sector Companies listed on the Indonesia Stock Exchange in 2020-2022. Keywords: Liquidity; Solvency; Activity; Profitability